Digital Transformation for Crisis Resilience in MSMEs: Evidence from Banten Indonesia - Marinus Gea; Sri Lestari (Yayasan Aya Sophia Indonesia, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in Banten, Indonesia face multifaceted crises encompassing economic shocks, digital disruption, and post-pandemic instability that threaten their operational viability and long-term sustainability. This qualitative case study investigates how digital transformation enables crisis resilience in MSMEs operating within crisis conditions. Drawing on in-depth interviews with 12 MSME owners and managers in Banten across manufacturing, culinary, and retail sectors, combined with documentary analysis, this research employs thematic analysis to examine organizational adaptation processes during crisis periods. The study reveals that digital transformation functions as a critical adaptive mechanism through which MSMEs enhance their sensing and response capabilities to external shocks. Key findings demonstrate that digital transformation operates through three primary mechanisms: operational reconfiguration via digital platforms and e-commerce, strategic flexibility through integrated information systems, and stakeholder collaboration facilitation via digital channels. Notably, the study identifies that digital transformation's effectiveness in building resilience is mediated by organizational learning capacity, leadership commitment, and institutional support mechanisms. This research contributes novel theoretical insights by operationalizing the relationship between digital transformation and crisis resilience through a dynamic capabilities lens applied to the Indonesian MSME context. Empirically, it provides evidence-based insights from Banten's MSME ecosystem during crisis conditions. Methodologically, it advances qualitative understanding of how MSMEs interpret and operationalize digital tools within crisis-constrained environments. The findings offer practical implications for MSME actors seeking to strengthen adaptive capacity, for policymakers designing support mechanisms, and for institutional development organizations facilitating inclusive digital transformation. The research concludes that sustainable crisis resilience in MSMEs emerges not merely from technology adoption, but from intentional organizational redesign that integrates digital capabilities with adaptive leadership and collaborative governance structures.